EXPLORING THE POSSIBILITIES OF INCREASING THE QUALITY OF NON-WOVEN FABRICS - Tadjibayev , Anvar Avazovich (Educational Research in Universal Sciences, 2024)
This paper explores the possibilities of improving the quality of non-woven fabrics through various techniques and processes. Non-woven fabrics are widely used in industries such as healthcare, automotive, and construction, and enhancing their quality can lead to better performance and durability. The study investigates potential methods for increasing strength, durability, and uniformity of non-woven fabrics, with a focus on improving the overall quality.